Intra-Household Wealth and Welfare Inequality in the US: Estimations from a Collective Model of Labor Supply - José Alberto Molina; J. Ignacio Gimenez-Nadal; Jorge Velilla (Institute of Labor Economics (IZA), 2018)
This paper analyzes the intra-household distribution of wealth and welfare in the United States, within a theoretical framework based on a collective model of labor supply, where household decisions are Pareto efficient, and spouses negotiate a sharing rule for non-labor income. Using the American Time Use Survey for the years 2003 to 2015, estimates show a positive correlation between individual wages and labor supply, while cross-wages go in the opposite direction. Additionally, we find that wives tend to be more altruistic in comparison to their husbands regarding the intra-household allocation of income, which leads to wealth inequalities. However, the intra-household processes appear to be efficient in terms of welfare, as increases in any source of household income are associated with decreases in intra-household inequality, as measured by the spouses' estimated indirect utility. Our results shed light on the spouses' wealth shares and the sharing rule guiding the individual allocations, which may be important in the design of policies aimed at alleviating poverty.
Keywords: D15; J22; 330; collective model; labor supply; sharing rule; intra-household inequality; welfare; American Time Use Survey